A numerical assessment of microtopographies with varied geometries in relation to biofouling control - Myan, Felicia Wong Yen; Min, Lam Kuo; Hong, Lim Chin; Walker, James (Taylor's University, 2018)
Biofouling is the unwanted attachment of organisms and microorganisms to a submerged surface. It is a natural phenomenon that results in negative impacts on man-made industries such as the marine industry, food industry, water treatment among others. Studies have shown that the application of surface topography with varied geometries and sizes have the potential to prevent biofouling. This research aims to assess microtopographies of varied geometries and shape in relation to biofouling control. The size and dimensions of the topographies were kept the same at 150 µm. This research is computational where simulations of flow in three-dimensional (3D) models were performed with ANSYS Fluent, a Computational Fluid Dynamics (CFD) software. With the aid of CFD, simulations of fluid flow in 3D models that consist of surface topographies with varied geometries and defined boundary conditions were conducted. The topographies investigated include pillars, octagonals, cross shaped grooves and square grooves. Hydrodynamic variations of interest that were analysed upon completion of the simulations include wall shear stress and velocity. Analysis of simulations show that the presence of topographies disrupt uniform flow and creates hydrodynamic fluctuations that discourage biofouling settlement. Simulations indicate that the pillars topography would likely have the best antifouling potential because it is the least likely to result in the formation of many vortices and also because shear stresses at the peaks of this topography are the highest among the four investigated topographies. © School of Engineering, Taylor’s University.